The Role Of Accounting Information Systems In Management Decision Making At PT. Kawi Pusaka Raharja (Wings) Bantaeng District - Nirwana, Nirwana; Abdul Muttalib; Wahyuni, Wahyuni (International Journal of Economic Research and Financial Accounting, 2023)
This study aims to determine the role of accounting information systems in management decision-making at PT Kawi Pusaka Raharja (Wings) Bantaeng Regency. This research is a type of qualitative descriptive research. Data collection is done by employing observation, interviews, and documentation. The data analysis method used is data reduction, data presentation, and conclusion drawing/verification. Based on the results of the research that has been done, it can be concluded that the accounting information system at PT Kawi Pusaka Raharja (Wings) Bantaeng Regency plays an important role in management decision-making because the accounting information system that has been computerized and the quality of the accounting information system used is very effective and efficient so that management, especially managers in the company, becomes easier in making decisions. Accounting information systems have played a very important role in decision-making at PT Kawi Pusaka Raharja (Wings) Bantaeng Regency despite the problems experienced in the accounting information system process, where often all activities and transactions within the company are hampered due to poor networks. However, this does not reduce the function of the accounting information system in decision-making.